Presidential Decree-Law No. 29 Of The Year 2015 On Increasing The Pensions As Of 1/7/2015 = قرار رئيس جمهورية مصر العربية رقم 29 لسنة 2015 بزيادة المعاشات اعتبارا من1-7-2015 - Egypt; The middle east library for economic services, translator. (2025)
presidential decree-law no. 29 of the year 2015 on increasing the pensions as of 1/7/2015 قرار رئيس جمهورية مصر العربية بالقانون رقم 29 لسنة 2015 بزيادة المعاشات اعتبارا من 1/7/2015